Descriptive Analysis of Real-World Data on Fingolimod Long-Term Treatment of Young Adult RRMS Patients - Ziemssen, Tjalf; Albrecht, Holger; Haas, Judith; Klotz, Luisa; Lang, Michael; Lassek, Christoph; Schmidt, Stephan; Ettle, Benjamin; Schulze-Topphoff, Ulf (Frontiers in Neurology, 2021)
Background: Fingolimod (Gilenya®) is approved for adult and pediatric patients with highly-active relapsing-remitting multiple sclerosis (RRMS). Objectives: The objective was to describe the effectiveness of fingolimod in young adults compared to older patients in clinical practice. Methods: PANGAEA is the largest prospective, multi-center, non-interventional, long-term study evaluating fingolimod in RRMS. We descriptively analysed demographics, MS characteristics and severity in two subgroups of young adults (≤20 and >20 to ≤30 years) and older patients >30 years. Results: Young adults had lower expanded disability status scale (EDSS) scores compared to older patients (1.8, 2.3 vs. 3.2) at baseline. Mean EDSS scores remained stable over 5 years in all subgroups. Young adults had higher annual relapse rates (2.0, 1.7 vs. 1.4) at study entry, which were reduced by approximately 80% in all subgroups over 5 years. The proportion of patients with no clinical disease activity in year 4 was 52.6%, 73.4% vs. 66.9% in patients ≤20, >20 to ≤30 years and >30 years, respectively. The symbol digit modalities test score increased by 15.25±8.3 and 8.3±11.3 (mean ± SD) from baseline in patients >20 to ≤30 and >30 years. Conclusions: Real-world evidence suggests a long-term treatment benefit of fingolimod in young RRMS patients.